MANAJEMEN PROGRAM AKSELERASI DI SMP PL DOMENICO SAVIO SEMARANG - Kartini, Justina Endang; Ismanto, Bambang (Kelola: Jurnal Manajemen Pendidikan, 2015)
This study aimed to describe the management acceleration program in terms of planning, organizing, actuating, and monitoring learning in PL Domenico Savio JuniorÂ High School. This research is a qualitative descriptive study. Subjects were principal,Â manager acceleration, acceleration secretary, and homeroom teacher. Results ofÂ research: Planning accelerated program in PL Domenico Savio Junior High SchoolÂ done by preparing teachers, finance, infrastructure, learners, curriculum, time, andÂ high school. Learning plan covering the syllabus and lesson plan contains learningÂ objectives, teaching materials, teaching methods, learning resources, and assessmentÂ of learning outcomes. Organization of human resources contained in the organizationalÂ structure of the school is equipped manager acceleration. Organizing acceleratedÂ learning includes the step before learning, implementation, and after learning. Teachers organize learning materials to learnersâ learning time. Acceleration managers manageÂ learning activities acceleration in school and outside of school. Actuating of acceleratedÂ program refers to the RPP and half of each subject program. Implementation of theÂ learning stages: introduction, core activities, and cover. Monitoring the accelerationÂ of learning is done directly by the students, parents of students, and managersÂ acceleration. Learners and parents provide input on school. Manager accelerationÂ control feasibility study. Principal using monitoring results into training materials forÂ teachers. Accelerated learning assessment carried out by the teacher. TeacherÂ evaluations are conducted by the principal and foundations. Reporting accelerated learning is done on the parents of learners.